Visiting Maril Turpin's Family Cabin At Bass Lake - Watkins, Howard::::::::: (1982)
Shirley Griffenhagen, Maril Turpin, Christine Watkins, Adam Watkins, Peggy Sanders in background ready to see fireworks All sitting on webbed nylon lounge chairs